EXISTING APPROACHES TO RISK ASSESSMENT OF REAL INVESTMENT PROJECTS: THEIR ADVANTAGES AND DISADVANTAGES - E. Bogomolova; А. Bering (Вестник университета)
Risk management is impossible without a systematic assessment of the significance level of identified project risks. Within the scope of this article, features of the various qualitative and quantitative methods of risk assessment of real investment projects are highlighted. This article analyzes some of the methods from the aspect of their advantages and disadvantages in application with the aim to facilitate the selection of the most convenient method for the particular project.